Combining ability analyses of grain yield and kernel micronutrient content in maize (Zea mays) - NANDAN, RISHAV; RASHMI, KUMARI; SANJAY, SAHAY; MANDAL, S S; SINGH, BIRENDRA (The Indian Journal of Agricultural Sciences, 2021)
The present study was aimed to assess the general combining ability of parents and specific combining ability of their crosses for yield and yield related traits. Nine inbred lines were crossed with two testers using line × tester mating design. Nine lines, two testers and 18 experimental hybrids were evaluated along with two checks in this study for grain yield and protein content, besides kernel micronutrients (phosphorous, caicium and iron) during kharif 2019 in a randomized block design at experimental farm of BAC, Sabour. The line CLQRCY44 and HKI1532 were found as good general combiner for grain yield and quality traits followed by DHOLI inbred 55 and CLO2450. Lines DHOLI inbred 55 and CML451 were found as good general combiner for earliness, lines CLQRCY44, CLO2450 and DHOLI 55 for quality traits like protein content, calcium content, phosphorous and iron content. Among the crosses, HKI1532 × 95IOWA (67.43 q/ha), LM13 × SUWAN (65.87 q/ha) and CML425 × SUWAN (63.30 q/ha) were the promising crosses for grain yield. CLO2450 × SUWAN and LM13 × SUWAN exhibited highly significant and desirable SCA effects for grain yield. CLO2450 × 95IOWA exhibited highly significant and desirable SCA effects for protein content. HKI1532 × 95IOWA (67.43 q/ha) was the promising hybrid for grain yield and micronutrient content. Therefore, these crosses can be utilized for developing high yielding micronutrient enriched hybrid varieties in maize (Zea mays L).